DEVELOPMENT OF A SUSTAINABLE WATER ADVENTURE TOURISM MODEL IN INDONESIA - R. A. Amalia Yunita; Arief Faizal Rachman; M. Husen Hutagalung; Rianto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study examines the management processes of water adventure tourism operators in Indonesia and their contribution to sustainable development. It specifically analyzes the effects of governance, environmental sustainability, and social equity and cultural vitality on economic prosperity and sustainable adventure tourism development, while also considering the moderating role of government policy and the mediating role of economic prosperity. The research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. Data were collected through purposive sampling from 130 water adventure tourism operators across six destinations in Indonesia. The findings reveal that governance does not directly influence economic prosperity or sustainable tourism development. However, government policy strengthens the positive relationship between governance and economic prosperity, although it does not moderate its effect on tourism development. Environmental sustainability shows no significant effect on economic prosperity but has a positive impact on sustainable tourism development, with no moderating role of government policy. In contrast, social equity and cultural vitality significantly and positively influence both economic prosperity and sustainable tourism development, although government policy does not moderate these relationships. Furthermore, economic prosperity positively affects sustainable tourism development but does not act as a mediator in the model. Overall, the study highlights the critical role of social and cultural dimensions in achieving sustainable tourism, while the role of government policy remains limited and selective.